Decision Support System for Hydro Power Plants in Amazon Considering the Cost of Externalities - Carvalho, Evelyn Gabbay Alves; Blanco, Claudio José Cavalcante; Duarte, André Augusto Azevedo Montenegro; Maués, Luiz Maurício Furtado (International Journal of Energy Economics and Policy, 2020)
Feasibility studies on Hydro Power Plants (HPPs) should adequately measure the values of the social, economic and environmental impacts (i.e., its externalities) of HPPs. In this case, the final cost of an energy generation project is lower than the actual value because the impacts are not appropriately assessed. Thus, the objective of this paper is to estimate the total cost of generated energy using a methodology capable of accounting for the cost of the externalities of hydroelectric plants. This study assesses the externality resulting from loss of fishing activity, an economic activity practised by a large part of a population affected by hydroelectric dam construction. To assess this externality, the opportunity cost method and a time series analysis are used to forecast future values. It is demonstrated that when considering only the externality resulting from the loss of fishing activity, the expected cost of energy production could increase significantly. This result indicates the need to calculate all the externalities caused by the implementation of a hydroelectric power plant (HPP) and to incorporate these actual values into the energy production cost, so the enterprise is sustainable and feasible. Our results also facilitate a realistic comparison with other sources of energy generation. Keywords: fishing activity; opportunity cost; forecast; Amazon. JEL Classifications: Q2, Q4. DOI: https://doi.org/10.32479/ijeep.8746